Reliability Prediction And Modeling: A Case Study Of Dry Gas Seal And Buffer Gas System On Compressor For Gas Transportation - Wan Mohd Syazwan Bin Wan Ibrahim, Wan Mohd Syazwan (Universiti Teknologi Petronas, 2008)

(untitled)
Improvement in compressor reliability in petrochemical, chemical and gas industry services will results in higher production revenue and significant savings in maintenance related cost. Centrifugal compressors play a major role in the successful operation of transporting hydrocarbons from offshore by compressed and boosted it to the onshore refinery facilities. To reach the onshore facilities, the pipeline system required several other compression stations to help boost the gas to the shore depending on the distance covered. The compressor is interconnected with the driver which will drive the compressor. Each compressor is supported with gas seal and buffer gas seal supply to deliver the dry gas to the mechanical seal install at the both end of the shaft. For the seal to function without any failure, the dry gas and buffer gas system has to have high reliability. The study conducted is to calculate the reliability of the compressor dry gas seal and buffer gas seal system which is used in the oil and gas industry and identify weather the system is reliable or not for the operation. The Pipping and Instrumentation Diagram (P&ID) of dry gas and buffer gas system of Baram compressor was converted to Reliability Block Diagram (RBD) which simplified and derived the mathematical model of both systems. Using Offshore Reliability Data Handbook 2002 (OREDA 2002), data on failure rate and reliability of each equipment was obtained. Finally, the mathematical model was simulated using the failure rate value and the overall gas seal system reliability is obtained.